An Adolescent’s Use of Veterinary Medicines: A Case Report Exploring Addiction - Kaggwa, Mark Mohan; Nuwamanya, Sympson; Ashaba, Scholastic; Rukundo, Godfrey Zari; Harms, Sheila (Journal of psychoactive drugs, 2021)
This case report describes a 17-year-old high school student serious suicide attempt using an injectable composite of veterinary medications (vitamins, vaccines, antibiotics, and antihelminthics) typically used to treat chickens. The use of this particular substance and the route of administration was novel as a method for suicide lethality and there have been no previous cases of this kind. However, this youth also developed chronic self-harming behaviors where she would repeatedly self-inject the veterinarian medication composite which included substances that were largely inert but did have a potential neuropsychiatric side effect profile that complicated her psychiatric presentation. In this context of chronically injecting a substance with unclear psychoactive properties, an interesting set of symptoms and behaviors emerged that required diagnostic clarification and interpretation. Diagnostic considerations for this youth included major depressive disorder with psychotic features, a possible emerging borderline personality disorder, post-traumatic stress disorder (PTSD), as well a possibility of an unknown substance use disorder using the veterinary medication composite. The purpose of this case study is to highlight the clinical course and explore sociocultural factors, including family and interpersonal relationships as contextually important variables.
Keywords: Addiction; depression; suicide; veterinary medications; borderline personality disorder; deliberate self-harm; Uganda